Redefinition of working aqueous two-phase systems: a generic description for prediction of the effective phase chemical composition for process control and biorecovery - Selvakumar, Pitchaivelu; Tau, Chuan Ling; Walker, Simon; Lyddiatt, Andrew (2010)
Aqueous two-phase systems (ATPS) have been widely adopted for the combined purpose of solid liquid separation, and recovery and purification of bioproducts such as proteins, viruses and organelles from biological feedstocks and fermentation broth. However, in spite of potential advantages over other techniques applied to concentrated biological feedstocks, ATPS have been applied at process scale only by a few industries and research establishments. ATPS are sensitive to loading with modest to extreme quantities of biological feedstock due to the contribution of that material to phase formation in combination with the conventional phase-forming chemicals. This causes problem associated with the definition and manipulation of loaded working systems, which may be addresses as in the present study with the aid of distribution analysis of radiolabel led analytes (DARA) in representative process samples. The present study focussed on establishing a generic description for characterising ATPS loaded with biological feedstocks and the redefinition of the biological feedstock loaded system composition in terms of phase forming chemical equivalents. This evaluation will be useful to achieve ATPS process implementation where phase recycle/reuse is adopted without compromise to process operations and consistent protein recovery performance.